Rapa’i Geurimpheng: The existence of Aceh traditional art, Indonesia - Syai, Ahmad; Jazuli, Muhammad; Wadiyo, Wadiyo; Utomo, Udi (Research Journal in Advanced Humanities, 2024)
Rapa’i Geurimpheng Art is a form of traditional art which comes from Aceh, Indonesia covering the music and dance show by using rapa’i musical instrument. This research aimed to reveal the role and challenges in the effort of Rapa’i Geurimpheng Art preservation in Ukee Village, Pidie Regency, Aceh Province as an unseparated cultural heritage from Aceh. The research method employed qualitative approach with deep interview as the main technique of the data collection. The respondents involved in this research were the local community members who had knowledge and direct experience in the practice of Rapa’i Geurimpheng Art included the musician, the community leader, and the custom figure. The collected data were analyzed thematically to identify the pattern, main finding, and challenge in the art preservation. The research results showed that Rapa’i Geurimpheng Art contained social and religious values that wanted to be delivered to the community. Those values were cooperation, honesty, discipline, and responsibility. The art preservation process was carried out through both formal and non formal education. One of the method was by carrying out a training at school with speakers from the art craftsmen to attract the young generation interest into it.